Appypie-Based Mobile Learning for ICT MGMP Teachers in Lima Puluh Kota - yeka Hendriyani; Hansi Effendi; Geovanee Farell; Vera Irma Delianti (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to improve the knowledge and skills of ICT MGMP teachers in Lima Puluh Kota in developing Appypie-based mobile learning media. The partner’s main problems included limited information technology skills, low competence in developing multimedia-based learning media, and the continued dominance of conventional instructional media such as textbooks, whiteboards, and basic PowerPoint presentations. To address these issues, the program offered structured training on developing Android-based learning media using Appypie. The activity was conducted at SMP Negeri 3 Harau and involved 20 teachers. The implementation method consisted of preparation, training sessions, guided practice, mentoring, and evaluation through observation, questionnaires, and product assessment. The results showed that the training improved participants’ understanding of mobile learning concepts and enhanced their practical skills in developing digital learning media using Appypie. The participants were also able to produce learning media products relevant to their own teaching materials. This program demonstrates that practice-based training and mentoring can effectively strengthen teachers’ professional capacity in producing innovative and relevant digital learning media for contemporary students..